Japan's economic security - Nobutoshi Akao; Maureen White (Intereconomics, 1981)
While bringing unprecedented prosperity to post-war Japan, her “economic miracle” at the same time led to greater vulnerability owing to a much higher degree of dependency on raw material imports and outlets for export goods. This was brought home to the Japanese by events in the early 1970's. As Japan's small land; poor natural resources and large population leave her no option but to continue to depend on foreign markets, she will have to seek economic security within the framework of mutual interdependence.
Keywords: 330; Japan